2004
DOI: 10.1111/j.1745-7599.2004.tb00369.x
|View full text |Cite
|
Sign up to set email alerts
|

The Need to Bleed: Women's Attitudes and Beliefs About Menstrual Suppression

Abstract: Advanced practice nurses play an important role in educating women about menstrual health. Clinicians can use this information to assess women's attitudes and beliefs about menstrual symptoms and to educate them about misconceptions. The FDA approved Seasonale in September 2003, the first dedicated OC created to reduce the number of menstrual cycles yearly. Women need to be educated about the pros and cons of suppression; some women will benefit from suppression, and others will consider it unnatural.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 10 publications
0
35
0
3
Order By: Relevance
“…Nonetheless, for many women, monthly bleeding is a sign of health, fertility, and of not being pregnant; conversely, the absence of monthly bleeding is often believed to be linked to disease [2][3][4]. A large body of published evidence is gathering to suggest that monthly menstruation can be avoided without any deleterious effect to health [4][5][6].…”
Section: Introductionmentioning
confidence: 93%
“…Nonetheless, for many women, monthly bleeding is a sign of health, fertility, and of not being pregnant; conversely, the absence of monthly bleeding is often believed to be linked to disease [2][3][4]. A large body of published evidence is gathering to suggest that monthly menstruation can be avoided without any deleterious effect to health [4][5][6].…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, there seems to be a correlation between severe menstrual pain, irregular menstrual cycles and heavy menstrual bleeding on the one hand and psychosocial stress on the other (Barnard, Frayne, Skinner & Sullivan, 2003;Yamamoto, 2009), which may result in a poorer health status (Barnard et al, 2003). Scholars indicate that women with a negative and bothersome experience of menstruation are more positive to menstrual suppression than women with more positive attitudes (Andrist, 2004;Johnston-Robledo, Ball, Lauta & Zekoll, 2003).…”
mentioning
confidence: 99%
“…Previous studies have assessed women's attitudes toward, and knowledge about, extended use of COCPs (Den Tonkelaar and Oddens, 1999;Glasier et al, 2003Glasier et al, , 2008Andrist et al, 2004), but little research has examined their actual experiences of continuous use. Moreover, the few studies that have assessed women's experiences have been limited in scope and have most often used adherence to COCPs as a 'proxy' measure of satisfaction (Edelman et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…While the acceptability of initiating, and continuing on, extended-use regimens has been reported as high, acceptability in these studies has been narrowly defined (usually as continuation), often established from retrospective reviews of medical records of women using extended COCP regimens (Sulak et al, 2002(Sulak et al, , 2004. There have also been many more studies of women's attitudes toward hypothetical use of extended-use pill regimes (Den Tonkelaar and Oddens, 1999;Glasier et al, 2003Glasier et al, , 2008Andrist et al, 2004) than of their actual use of continuous COCPs. In a Cochrane review of use of extendedcycle versus standard use of COCPs, the authors concluded that further research on women's satisfaction and menstrual-associated symptoms was needed (Edelman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%